Revisão taxonômica do gênero Deltochilum Eschscholtz, 1822 subgênero Deltohyboma Lane, 1946 (Coleoptera : Scarabaeidae : Scarabaeinae) - González Alvarado, Fabio Arturo (2020)
The initial aim for thisthesis wasto taxonomically review the dung beetles (Scarabaeinae: Scarabaeinae: Coleoptera) of the subgenus Deltohyboma Lane, 1946. The subgenus, the most speciose out of the eight currently valid subgenera of Deltochilum Eschscholtz, 1822 (43 valid species before the start of this study), has a Neotropical distribution, mainly South American, and has both coprophagous and necrophagous habits. It was thought that, by the end of the current study, the modern review of the genus Deltochilum would be completed (an effort started over ten years ago). However, the amount of new species found in the subgenus (over 200) leading to an added complexity for the revision, meant it was not possible to complete the revision in the allocated time frame. Nonetheless, great progress is presented here, including the necessary foundations that will enable the completion of such a revision in the near future. The methodology used here is that traditionally used for taxonomic revisions based on comparative morphology. 9,800 specimens were studied of which 1,200 had their genitalia (mainly for males) extracted, structure-complex not studied for this group up until now. The specimens studied are deposited in 19 national and international colections. Of the 212 found, 88 are described in the present study, 69 of which are new species (Chapters 1-3). Aside from the description of a new endemic genus to the Brazilian Mata Atlântica (Chapter 4), lectotypes are designated for seven species and one previously synonimised species is revalidated. In Chapter 1 the subgenus is presented and described; 19 informal species groups are proposed and outlined, with a single species left as incertae sedis; two keys (one for both males and females and another for males only) for group identification are provided, as well as diagnoses and distribution for each of the groups.; taxonomic revision of seven of these groups, including identification keys, diagnoses, descriptions and distribution data for all the species of said groups are provided. In this Chapter (1) 43 species are described, 36 of which are new. In Chapter 2, the guyanense species-group is taxonomically revised. Identification keys, diagnoses, descriptions and the distribution of the 25 species, of which 20 are new, are provided. In Chapter 3, the irroratum speciesgroup is taxonomically revised. Identification keys, diagnoses, descriptions and the distribution of the 20 species, of which 13 are new, are provided. Chapters 1-3 are illustrated by 114 figures comprising (mainly) photographs, schematic drawings and distribution maps. Chapter 4 is illustrated by five figures. It is believed that the separation into informal species-groups will assist in the identification and the furtherance of the taxonomic revision of D. (Deltohyboma) as well as the highlight of important taxa for future phylogenetic studies of the genus Deltochilum. Such studies will help elucidate the phylogenetic relationships of the genus within Deltochilini (which remain unknown); the relationships of the eight subgenera, as well as; the relationships of the proposed speciesgroups. Lastly, after this study, the subgenus D. (Deltohyboma) now encompasses 123 valid species, increasing the known species for Deltochilum to 182. 130 species remain undescribed, for now.